Defining and measuring blood donor altruism: a theoretical approach from biology, economics and psychology - Evans, R.; Ferguson, E. (Wiley, 2014)
Background and Objectives While blood donation is traditionally described as a behaviour motivated by pure altruism, the assessment of altruism in the blood donation literature has not been theoretically informed. Drawing on theories of altruism from psychology, economics and evolutionary biology, it is argued that a theoretically derived psychometric assessment of altruism is needed. Such a measure is developed in this study that can be used to help inform both our understanding of the altruistic motives of blood donors and recruitment intervention strategies.